MYH9‐macrothrombocytopenia caused by a novel variant (E1421K) initially presenting as apparent neonatal alloimmune thrombocytopenia. Issue 4 (29th December 2017) - Samelson‐Jones, Benjamin J.; Kramer, Paula M.; Chicka, Michael; Gunning, William T.; Lambert, Michele P.
Abstract: MYH9 ‐related disease is a rare cause of thrombocytopenia. We report an infant girl who presented with severe thrombocytopenia at birth and was initially diagnosed with and treated for neonatal alloimmune thrombocytopenia. However, persistent thrombocytopenia led to the suspicion of congenital thrombocytopenia and subsequent identification of a novel variant in MYH9 (E1421K). In silico analysis strongly predicts that this is a disruptive substitution. Immunofluorescent analysis of neutrophils demonstrates abnormal aggregates of MYH9 protein. This case also suggests that a very high immature platelet fraction (≥40%) may be useful for rapidly differentiating MYH9 ‐related disease from other causes of neonatal thrombocytopenia.